2015
DOI: 10.1155/2015/595829
|View full text |Cite
|
Sign up to set email alerts
|

Human Leucocyte Antigen‐G (HLA‐G) and Its Murine Functional Homolog Qa2 in the Trypanosoma cruzi Infection

Abstract: Genetic susceptibility factors, parasite strain, and an adequate modulation of the immune system seem to be crucial for disease progression after Trypanosoma cruzi infection. HLA-G and its murine functional homolog Qa2 have well-recognized immunomodulatory properties. We evaluated the HLA-G 3′ untranslated region (3′UTR) polymorphic sites (associated with mRNA stability and target for microRNA binding) and HLA-G tissue expression (heart, colon, and esophagus) in patients presenting Chagas disease, stratified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 76 publications
(65 reference statements)
0
12
0
Order By: Relevance
“…The induction of Qa2 gene expression during the acute phase may allow a better control of tissue damage caused by the inflammatory process due to an exacerbated immune response triggered against the T. cruzi parasite. This may counterbalance the action of proinflammatory molecules, such as INF‐ γ and NOS‐2 , which were also shown to be induced during acute T. cruzi infection …”
Section: Hla‐g Molecule In Parasitic Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…The induction of Qa2 gene expression during the acute phase may allow a better control of tissue damage caused by the inflammatory process due to an exacerbated immune response triggered against the T. cruzi parasite. This may counterbalance the action of proinflammatory molecules, such as INF‐ γ and NOS‐2 , which were also shown to be induced during acute T. cruzi infection …”
Section: Hla‐g Molecule In Parasitic Disordersmentioning
confidence: 99%
“…101 Dias et al were the first to investigate the role of HLA-G in Chagasic patients and its functional murine homolog Qa2 in experimental T. cruzi infection as well as their impact on Chagas disease progression and clinical expression. 88 They evaluated HLA-G 3 0 UTR polymorphisms and HLA-G tissue expression (heart, colon and esophagus) in 138 Chagas disease patients with well-recognized chronic clinical forms and compared them to 39 asymptomatic patients exhibiting positive serology for T. cruzi antigens (indeterminate form). They also compared patients to 155 healthy individuals who had never been exposed to the specific infectious agent.…”
Section: American Trypanosomiasismentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, HLA non-classical class I genes have not been studied yet. Nevertheless, studies in other parasitic diseases found HLA-G 3' UTR polymorphisms exhibiting distinct patterns of associations with both Human African Trypanosomiasis (HAT) and American Trypanosomiasis (Chagas disease) Dias et al 2015;Sabbagh et al 2018).…”
Section: Host Geneticsmentioning
confidence: 99%
“…High levels of sHLA-G are also associated with increased susceptibility to malaria (Sadissou et al 2014;D'Almeida et al 2016D'Almeida et al , 2017 and to human African trypanosomiasis (HAT) (Gineau et al 2016). In contrast, decreased membrane-bound HLA-G has been reported in placenta of patients infected with P. falciparum (Sartelet et al 2005) and in heart and colon of patients presenting Chagas disease (Dias et al 2015).…”
mentioning
confidence: 99%